SISTESIS GRAFENA DARI BAHAN TEMPURUNG KELAPA, LONTAR DAN KEMIRI MENGGUNAKAN METODE HUMMER TERMODIFIKASI - Patunrengi, Iswadi Ibrahim; Zelviani, Sri; Fuadi, Nurul (SAINFIS: Jurnal Sains Fisika, 2022)
Research has been conducted that aims to find out the graphene characteristics of coconut shell, hazelnut shell and lontar shell and to find out the effect of material type on graphene conductivity value. Graphene is one or more layers of carbon atoms that make up the hexagonal structure and has emerged as the leader of nanoscale     two-dimensional carbon materials. Graphene has unique physical and chemical properties such as quantum effects as well as electron mobility and high conductivity. Due to its unique nature, graphene has sparked enormous interest in all fields such as electronic and energy devices, catalysts, sensors, and capacitors. In the manufacture of graphite carbon using a strong acid batteryr, phosphoric acid (H3PO4) then continued with the synthesis of graphene oxide using the modified hummer method which is then reduced to graphene. Based on research conducted obtained data for graphite carbon has met the Indonesian National Standard (SNI-06-3730-1995). X-Ray Diffraction (XRD) characterization produced the difractogram pattern with the highest peak values in each sample of 44.05620, 44.05370 and 44.05130 respectively and produced an amorphous shape. Furthermore, the characterization of Fourier Transform Infra-Red (FTIR) is known to have a function group in each sample, namely O-H, C = O, C = C, and C-O. The results of electrical conductivity tests conducted on graphene samples of coconut shell, hazelnut shell and lontar shell obtained values of 0,0040 S/cm, 0,0037 S/cm dan 0,0041 S/cm, respectively.